Appressed, directed and silicified trichomes of the kudzu climbing vine. (2nd August 2022) - Seo, Dahye; Park, Junhyung; Kim, Ki Woo
Abstract: Kudzu ( Pueraria montana var. lobata ) is becoming one of the most prevalent climbing vines in urban forests. Here, surface characteristics of kudzu leaves and stems are investigated using field-emission scanning electron microscopy and X-ray microanalysis. The leaf and stem surfaces were characterized by different types of trichomes. No adhesive pads, modified hooks or tendrils were found on kudzu vines. Trichomes on the leaves and stems of kudzu could be categorized into (i) complex bulbous glandular trichomes and (ii) needle-shaped nonglandular trichomes (NSNGTs). Two morphotypes of the nonglandular trichomes were present on the stems: (i) long hairy nonglandular trichomes and (ii) short NSNGTs. The leaf trichomes were appressed and oriented in an uphill direction, whereas the stem trichomes were appressed and oriented in a downhill direction. This opposite trichome orientation appears to facilitate climbing and prohibits slipping of kudzu vines through differential friction between the plants and the kudzu vines. X-ray microanalysis revealed a distinct accumulation of silicon in the leaf and stem trichomes. These results suggest that appressed, directed and silicified trichomes may contribute to the twining behavior of kudzu vines.